Research Progress of UiO-66-Based Electrochemical Biosensors - Wu, Ming; Zhang, Qi; Zhang, Qiuyu; Wang, Huan; Wang, Fawei; Liu, Junmei; Guo, Liquan; Song, Kai (Frontiers in Chemistry, 2022)
UiO-66, as a member of the MOFs families, is widely employed in sensing, drug release, separation, and adsorption due to its large specific surface area, uniform pore size, easy functionalization, and excellent stability. Especially in electrochemical biosensors, UiO-66 has demonstrated excellent adsorption capacity and response signal, which significantly improves the sensitivity and specificity of detection. However, the existing application research remains in its infancy, lacking systematic methods, and recycling utilization and exclusive sensing of UiO-66 still require further improvement. Therefore, one of the present research objectives is to explore the breakthrough point of existing technologies and optimize the performance of UiO-66-based electrochemical biosensors (UiO-66-EBs). In this work, we summarized current experimental methods and detection mechanisms of UiO-66-EBs in environmental detection, food safety, and disease diagnosis, analyzed the existing problems, and proposed some suggestions to provide new ideas for future research.